Ethnocategories and Andean Metallurgy - Lechtman, Heather (Pontificia Universidad Católica del Perú. Fondo Editorial, 2003)
IN HIS FOREWORD to the volume The Social Dynamics o/ Technology, Tim Ingold (1999) challenges us to specify the claims we make in using the term technology and to justify those claims. Here is my claim. Ethnocategories by which people order experience are rendered through technological behavior just as they are rendered linguisticall y (Lechtman r996a, r996b). Appropriate study of the materials technologies people used to produce objects will allow archaeologists to identify these categories and to investigate their presence and, thereby, their utility as organizing principles in other spheres of social activity
Páginas [115]-128
Keywords: Metalurgia--Perú--Historia--Época prehispánica; Tecnología--Perú--Historia--Época prehispánica; https://purl.org/pe-repo/ocde/ford#6.02.00